Transformações em aulas de leitura e de análise linguística: percursos de professoras - Garcia, Vera Barros Brandão Rodrigues (Universidade Federal do Tocantins, 2017)
In this research we investigated how literacy activities mediated by genre can be developed in a class considered outdated because the students have difficulties in reading and writing. The action research is carried out in an Elementary Public School of Maraba, in a class of 6th year (5th grade) of the Elementary School. We also intend to investigate how these activities can help in the development of reading practices, textual production and linguistic analysis of these students with learning difficulties. In planning for intervention in the classroom, we developed a teaching unit which consists of lesson plans guided by pedagogical proposal called Curriculum Circuit Mediated by Genre (CCMG). We intend to observe the development of these activities, the involvement and participation of students in the proposed classes, we still want to experience and evaluate the methodology at each step of the CCMG and then answering the main question of this action research: how the activities of reading and linguistic analysis mediated by CCMG can cause changes in the teaching and learning of Portuguese language? We characterize this work as an action research because it is not simple data collection or reports to be filed, thus, we intend to play an active role in the reality of the observed facts. This research is also characterized as a case study because it investigate and thoroughly explore the teaching unit applied in pedagogical intervention. To support the proposed intervention we review some applied studies regarding to genres, literacy studies; as well as Applied Linguistics and Systemic Functional Linguistics. The results showed that the Teaching Unit implemented during the educational intervention was developed as a process of reorienting teaching practice and learning promoter. The results showed that the Teaching Unit implemented during the educational intervention was developed as a process of reorienting teaching practice and learning promoter. Considering the presented reflections, we highlight the need to develop applied research on pedagogical practices, involving teachers in service. Due to the multifaceted nature of the problem, we find that the overshoot depends on joint actions within the school scope, academic scope and in the public policy.